Quantum Entanglement and Non-Locality: Experimental Advances and Theoretical Implications - Anil Kumar (Innovative Research Thoughts, 2017)
Quantum entanglement and non-locality are urgent peculiarities in quantum mechanics, showing the interconnectedness of particles paying little heed to separate and testing old style ideas of locality. This paper audits critical experimental progressions and theoretical improvements there. It covers significant analyses, mechanical developments in entanglement estimation, and their translations, as well as advances in the understanding of non-locality and its coordination with quantum data hypothesis. The functional implications for quantum processing and cryptography are talked about, close by philosophical contemplations and future examination bearings. The discoveries highlight the significant effect of quantum entanglement on current material science and altering technology potential.